La reconnaissance de l’homoparenté au Québec. Lorsque les stratégies de mobilisation de la communauté rencontrent l’avant-gardisme de l’État - Côté, Isabel; Lavoie, Kévin (Revue des politiques sociales et familiales, 2018)
Résumé Cet article retrace les jalons historiques ayant mené à l’institutionnalisation de l’homoparenté au Québec et met en lumière la synergie entre les revendications d’associations gaies et lesbiennes et les interventions étatiques de l’appareil gouvernemental. La décriminalisation de l’homosexualité au Canada en 1969, puis l’ajout de l’orientation sexuelle comme motif illicite de discrimination dans la Charte québécoise des droits et libertés en 1977 ont posé les bases juridiques sur lesquelles s’est ancrée la reconnaissance des couples de même sexe et des familles homoparentales aux tournants du nouveau millénaire. Les stratégies de mobilisation déployées par les groupes militants se sont alors inscrites dans les filières institutionnelles de l’action publique, à la rencontre des interventions progressistes de l’État québécois. L’analyse rétrospective de cette lutte offre une meilleure compréhension de la transformation des représentations familiales contemporaines et des débats actuels en matière de filiation.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; maternité; parentalité; premier cycle; privilèges; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2262; soc2264; sociologie; systèmes d'oppressions; thématiques

Queer Theory and Sociology: Locating the Subject and the Self in Sexuality Studies - Isaiah Green, Adam (Sociological Theory, 2007)
In this paper, I revisit the relationship of queer theory and sociology in order to address some critical issues around conceiving the subject and the self in sexualities research. I suggest that while sociology and queer theory are not reducible to each other, sociology has its own deconstructionist impulse built into pragmatist and symbolic interactionist analyses of identity and subjectivity that is often overlooked by or reinvented through queer theory. But, conversely, queer theory has a very specific deconstructionist raison d'etre with regard to conceiving the sexual subject that marks its key departure from Foucault and sociology more generally. This deconstructionist mandate, by definition, moves queer theory away from the analysis of self and subject position—including those accruing from race, class and gender—and toward a conception of the self radically disarticulated from the social. This “anti-identitarian” position has been a source of criticism among some sociologists who find in queer theory an indefensible “refusal to name a subject” ( Seidman 1993:132). But this criticism, I suggest, stems from a misplaced effort to synthesize queer theory and sociology when, in fact, the two approaches to the subject are founded on incommensurable methodological and epistemological principles. Rather, I argue that the very promise of queer theory rests in a strong deconstructionism that exists in tension with, rather than as an extension of, sociological approaches to the self
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; premier cycle; périodes historiques; queer; sciences humaines; soc2014; sociologie; thématiques

Des droits à reconnaître: les lesbiennes face à la discrimination - Bonneau, Micheline; Demczuk, Irène (Collection Les Entêtées, 1998)
Regroupant recherches et analyses, témoignages et récits personnels, ce livre rend compte de la discrimination vécue par les lesbiennes. Malgré que le Québec ait adopté une Charte des droits de la personne qui interdit toute discrimination basée sur l'orientation sexuelle, il faut reconnaître que l'adoption de ce principe d'équité n'a pas fait disparaître toute trace d'hétérosexisme dans la société. Les lesbiennes ne bénéficient pas encore d'une égalité juridique formelle, encore moins réelle.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; lesbophobie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; shm4000; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis